Exploiting Radiation Therapy to Restore Immune Reactivity of Glioblastoma - De Martino, Mara; Padilla, Oscar; Daviaud, Camille; Wu, Cheng-Chia; Gartrell, Robyn D.; Vanpouille-Box, Claire (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is among the most aggressive of brain tumors and confers a dismal prognosis despite advances in surgical technique, radiation delivery methods, chemotherapy and tumor-treating fields. While immunotherapy (IT) has improved the care of several adult cancers with previously dismal prognoses, monotherapy with IT in GBM has shown minimal response in first recurrence. Recent discoveries in lymphatics and evaluation of blood brain barrier offer insight to improve the use of ITs and determine the best combinations of therapies, including radiation. We highlight important features of the tumor immune microenvironment in GBM and potential for combining radiation and immunotherapy to improve prognosis in this devastating disease.